The Influence of Organizational Culture on the Implementation of Digital Marketing Strategies in Duck Egg Farming MSMEs in Soppeng Regency - Mansur Mansur; Yuli Sartika; Firda Zalzabillah; Intan Nur’aeni; Puji Rahmah (GENTARA: management and accounting research, 2026)
This study aims to analyze the influence of organizational culture on the implementation of digital marketing strategies in laying duck MSMEs. The development of digital technology has encouraged business actors to use social media, marketplaces, and online promotions to expand market reach and increase sales. However, the success of such strategies is not determined solely by technological capability, but also by organizational culture, which includes the values, norms, and work behaviors of business members. This study uses a quantitative approach with a survey method involving laying duck MSME actors. Data were collected through questionnaires and analyzed using simple linear regression to examine the effect of organizational culture on digital marketing implementation. The results indicate that an innovative, collaborative, and adaptive organizational culture has a positive effect on the successful implementation of digital marketing strategies. In addition, online promotion has been proven to increase customer reach and strengthen business competitiveness, consistent with the findings of Puji Rahmah, Andi Adawiah, Asnia Minarti, Asmini, and Muchlis Abbas in their study on online promotion at Galery Café Soppeng. Therefore, organizational culture plays an important role in supporting digital marketing transformation in laying duck MSMEs